Legal, Procedural and Social Aspects of Land Valuation in Land Consolidation: A Comparative Study for Selected Central and Eastern Europe Countries and Turkey - Ela Ertunç; Zlatica Muchová; Hrvoje Tomić; Jaroslaw Janus (Land, 2022)
The article presents the results of the analysis of the legal and practical aspects of the implementation of land value maps for land consolidation in four countries: Slovakia, Croatia, Poland and Turkey. The discussion indicated that it is not possible at present to construct fully universal methods of automatic earth valuation for LC. The reason is that there are too many different approaches to land value mapping. Identification of areas with similar characteristics (valuation factors) needs to be conducted prior to valuation of individual parcels. In both cases, the agronomic value from the farmer’s point of view is the key valuation criterion. It was pointed out that achieving versatility of algorithms can occur only as a result of extensive parameterisation of the developed models, both in terms of the number of factors considered, as well as the manner and strength of their interaction. The development directions of land valuation mass methods should proceed with the widest possible scope of public participation determining the principles of this valuation, which increases the level of acceptance of both the result of the land valuation itself and the subsequent effects of the land consolidation project.